A water-stable luminescent Zn-MOF based on a conjugated π-electron ligand as an efficient sensor for atorvastatin and its application in pharmaceutical samples. Issue 15 (22nd March 2022) - Rosales-Vázquez, Luis D.; Valdes-García, Josue; Germán-Acacio, Juan M.; Páez-Franco, José C.; Martínez-Otero, Diego; Vilchis-Nestor, Alfredo R.; Barroso-Flores, Joaquín; Sánchez-Mendieta, Víctor; Dorazco-González, Alejandro
Abstract : In this work, a novel water-stable 3D porous metal–organic framework was synthesized, structurally determined by single-crystal X-ray diffraction, and studied in-depth as a luminescent sensor for a series of statins and common biological ions in 20% aqueous ethanol. Abstract : Atorvastatin is amongst the most worldwide-prescribed drugs for cholesterol-lowering treatment. In this work, a novel water-stable 3D porous metal–organic framework [Zn3 (Htptc)2 ]·(H2 O)1.3 ·(CH3 CH2 OH)3.1 n, 1 (H4 tptc= terphenyl-3, 3′′, 5, 5′′-tetracarboxylic acid) was synthesized, structurally determined by single-crystal X-ray diffraction, and studied in-depth as a luminescent sensor for a series of statins and common biological ions (oxyanions, dicarboxylates, citrate, and adenosine 5′-triphosphate) in 20% aqueous ethanol. The luminescence of 1 can be effectively quenched by atorvastatin ( K SV = 1.40 × 10 5 M −1 ) with a pronounced selectivity over other typical statins such as fluvastatin, pravastatin, and rosuvastatin. The efficient quenching response exhibits excellent selectivity even in the presence of coexisting species in blood plasma and urine with a detection limit of 4.2 μmol L −1 . On the basis of multiple spectroscopic tools (fluorescence, UV-Vis, powder X-ray diffraction, lifetimes), the crystal structure of 1, SEM observations, EDS analysis, and DFT calculations, the sensing mechanism is proposed via a static-complexation PET process driven through π-stacking interactions between π-electron-rich terphenyl ligand and two aromatic rings from the atorvastatin. Neutral aqueous-phase dispersions of 1 allow for the detection of atorvastatin in real pharmaceutical samples. The utilization of MOFs-based materials as luminescent sensors for selective and sensitive detection of atorvastatin has not been explored till now.